Effects of pretreatments on the structure and functional properties of okara protein. (May 2019) - Tao, Xia; Cai, Yongjian; Liu, Tongxun; Long, Zhao; Huang, Lihua; Deng, Xinlun; Zhao, Qiangzhong; Zhao, Mouming
Abstract: Different pretreatments (homogenization, ultrasonic and steam-cooking treatments) before an alkaline extraction were employed to extract okara protein (OP) from defatted okara (residue left after extraction of the soy oil and water extractable fraction used to produce soybean protein isolates). The structure and functional properties of OPs subjected to pretreatments were determined. Analysis of fourier transform infrared spectroscopy (FTIR) revealed that the pretreatments had little effect on the secondary structure of OP. However, the tertiary structure of OP unfolded upon homogenization pretreatment and steam-cooking pretreatment, and the latter could lead to the increase in surface hydrophobicity (H0 ) of OP due to the exposure of hydrophobic groups resulted from partial unfolding, as demonstrated by fluorescence spectra. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) suggested that homogenization pretreatment and ultrasonic pretreatment did not destroy the subunit components of OP, but steam-cooking pretreatment could make OP denature and mostly degrade into small subunits because of higher temperature. Moreover, the changes in structure of OP significantly affected its functional properties. Results indicated that OP obtained by homogenization pretreatment exhibited the highest foaming ability index (FAI), while that of by ultrasonic pretreatment showed the highest foaming stability index (FSI), viscosity and emulsion stability. Steam-cooking pretreatment promoted the solubility and water holding capacity (WHC) of OP to the most extent. It should also be noticed that in comparison with commercial SPI, OP showed looser tertiary structure, higher H0 and similar SDS-PAGE pattern except for the detect of a glycoprotein, Bg 7S, which altogether resulted in better functional properties. In summary, OP has great potential to be applied in food area, especially in emulsifying agent and foam system. Graphical abstract: Image 1 Highlights: Different pretreatments were employed to extract OP from defatted okara before an alkaline treatment. Homogenization pretreatment disrupted the tertiary structure of OP, thus enhancing the FAI of OP. Ultrasonic pretreatment involved in rapid molecule movement, which considerably improved the FSI, viscosity and emulsion stability of OP. Steam-cooking pretreatment significantly increased H0 of OP and made its structure looser, thereby promoting the solubility and WHC of OP. OP presented looser tertiary structure, higher H0 and similar SDS-PAGE pattern except for the detect of Bg 7S, which altogether resulted in better functional properties in comparison with commercial SPI.